Pendampingan Masyarakat Terhadap Usaha Peternak Ayam Petelur Di Desa Kertagena Laok Untuk Meningkatkan Ekonomi Desa - Hoirun Nahdiyah; Fitriyah, Lailatul; Rafiah, Khofidhatur (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Some of the people of Kertagena Laok Village have professions as chicken breeders. In this business, chicken farmers in Kertagena Laok Village sell eggs from their livestock business. The chicken farming business in this village has an obstacle in terms of marketing, namely the existence of egg entrepreneurs outside Java who export their eggs to Madura. Based on this problem, the community in Kertagena Laok Village needs to be empowered and needs social assistance. So this time's service activity is based on community empowerment through assistance to improve marketing. So the method used to solve this problem is through initial observation/problems, Forum Group Discussion, community education, science and technology diffusion and training. The aim of this activity is to improve the village economy, awareness and participation of village communities in building a better village economy. Providing knowledge or new ways in developing marketing for chicken farms to be more focused in their farming business, increasing yields and overcoming problems or failures, willing to accept new ways that are more efficient and successful.